2004
DOI: 10.1128/mcb.24.7.3036-3047.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Chromatin-Mediated Restriction of Nuclear Factor 1/CTF Binding in a Repressed and Hormone-Activated Promoter In Vivo

Abstract: Mouse mammary tumor virus (MMTV) promoter-driven transcription is induced by glucocorticoid hormone via binding of the glucocorticoid receptor (GR). The MMTV promoter also harbors a binding site for nuclear factor 1 (NF1). NF1 and GR were expressed in Xenopus oocytes; this revealed GR-NF1 cooperativity both in terms of DNA binding and chromatin remodeling but not transcription. A fraction of NF1 sites were occupied in a hormone-dependent fashion, but a significant and NF1 concentration-dependent fraction were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 52 publications
4
33
0
Order By: Relevance
“…We previously showed that NF1 binds to the MMTV promoter within a wide range of intranuclear concentrations but did not have any effect on MMTV transcription. However, NF1 did stimulate MMTV basal and hormone-induced transcription when coexpressed with Oct1 (18). This posed the question of to what extent different Oct1 concentrations affected the hormone-activated MMTV transcription.…”
Section: Nf1 and Dose-dependent Oct1mentioning
confidence: 96%
See 4 more Smart Citations
“…We previously showed that NF1 binds to the MMTV promoter within a wide range of intranuclear concentrations but did not have any effect on MMTV transcription. However, NF1 did stimulate MMTV basal and hormone-induced transcription when coexpressed with Oct1 (18). This posed the question of to what extent different Oct1 concentrations affected the hormone-activated MMTV transcription.…”
Section: Nf1 and Dose-dependent Oct1mentioning
confidence: 96%
“…In vitro nucleosome reconstitution experiments with MMTV LTR DNA from the B-nucleosome region demonstrated a strongly preferred frame of rotational positioning (16,17) that was similar to the rotational position seen in vivo (13,18). The in vitro nucleosome reconstitution experiments also indicated a preferred translational nucleosome positioning similar to the organization seen in vivo, but they were conducted on rather small DNA segments (16,17,19,20).…”
mentioning
confidence: 88%
See 3 more Smart Citations